Wounded little gods a novel - Victoria, Eliza 1986- (Tuttle Publishing, 2022)
Regina was born and raised in the small town of Heridos, where gods and spirits walked the earth. Until they didn't. Ten years ago, the town's harvest failed and the people, believing the gods had abandoned them, left their farms and moved on. Now living in the city, Regina has a strange and disturbing conversation with a new colleague, Diana. Then, mysteriously, Diana disappears. A few days later, Regina finds a folded piece of paper in her bag. In Diana's handwriting are two names and a strange map that will send Regina back to her home town. In her quest to find Diana, she encounters rumors of genetic experiments, stumbles upon a strange facility that no one seems to know about, finds herself in places that don't exist, and discovers that people aren't who they seem to be and that the strange events in her town are closer to home than she ever knew.